Arabic Language Education Assessment through International Experiences: A Comparative Analysis: تقويم تعليم اللغة العربية من خلال تجارب دولية: التحليل المقارن - ElMeftahy, Nadia; Ahmiani, Otman (Journal of Arabic Language Learning and Teaching (JALLT), 2025)
This study explores the evolving role of educational assessment in enhancing the learning process, shifting from merely measuring academic achievement to a comprehensive tool for evaluating all educational aspects. Using an analytical approach, the research reviews relevant literature and applies this analysis to practical models in educational institutions. The findings highlight the importance of developing integrated assessment systems that leverage data analysis to provide effective feedback to students, teachers, and educational institutions. The study also reveals the strong connection between assessment and modern pedagogies, where each educational approach requires specific assessment tools. Key findings emphasize the need to foster excellence and creativity among learners and illustrate how assessments can drive the development of educational practices. This research offers both theoretical and practical frameworks for improving assessment practices in educational settings. Additionally, it provides actionable recommendations for enhancing educational quality through optimal use of data and assessment. Ultimately, the research contributes to modern education by introducing new tools and methods for evaluating learning, improving educational decision-making, and strengthening the teacher's role as a facilitator of learning.